Popular music, psychogeography, place identity and tourism: The case of Sheffield. (April 2014) - Long, Philip
Tourism and cultural agencies in some English provincial cities are promoting their popular music 'heritage' and, in some cases, contemporary musicians through the packaging of trails, sites, 'iconic' venues and festivals. This article focuses on Sheffield, a 'post-industrial' northern English city which is drawing on its associations with musicians past and present in seeking to attract tourists. This article is based on interviews with, among others, recording artists, promoters, producers and venue managers, along with reflective observational and documentary data. Theoretical remarks are made on the representations of popular musicians through cultural tourism strategies, programmes and products and also on the ways in which musicians convey a 'psychogeographical' sense of place in the 'soundscape' of the city.